Identificação de pontos de corte da circunferência do pescoço para determinação dos níveis de excesso de peso e predição do risco cardiometabólico em adolescentes - Souza, Márcia Ferreira Cândido de (2016)
High neck circumference can indicate weight excess and metabolic risk. Based in this evidence, the present work has as purpose identify the cut-off points of neck circumference (NC) for the determination of overweight and prediction of cardiometabolic risk in adolescents. A transversal study with students between 12 and 17 years old in public and private schools of Aracaju and Nossa Senhora do Socorro, Sergipe was carried out. Demographic, anthropometric (weight, height, body mass index (BMI), neck circumference (NP) and waist cirumference (WC)) biochemical, blood pressure (BP) data of the adolescents studied were collected. Cardiometabolic risk were evaluated according to the PDAY risk score criteria. For descriptive analysis the median, mean, standard deviation and frequencies of the variables anthropometric, demographic, biochemical and BP were calculated. The Mann-Whitney test for comparison of data among groups of adolescents by gender and age. The Spearman correlation coefficient and multiple regresão analysis were used to evaluate the association between CP and the anthropometric, biochemical and BP. From ROC curve the predictive validity of NC on the identification of overweight and cardiometabolic risk was analyzed. The samples were composed of 1474 teenagers with average age of 14.59 ± 1.57 years, being 55.3 % of females. NC was positively correlated with other adipose indicators (BP, HDL-cholesterol, insulin, fasting glycemia and glycosylated hemoglobin) and was the only indicator that significantly associated insulin (p=0.02). the cut-off points of NC determined by the study for the identification of overweight and obesity in males of 12 to 14 years old were, respectively, 34.1 cm and 34.9 cm for males and 32.05 and 33.85 for females. For males of 15 to 17 years old, the cut-off point for overweight and obesity were 36.8 cm and 38.4 cm, and for females were 32.9 cm and 35.8 cm. The NC cut-off points for cardiometabolic risk prediction were: puberal stage (feminino: 31.02 cm; male: 32.17 cm) and post puberal (female: 35.62 cm; male: 36.62 cm). NC presented significant correlation with other adiposity indicators being used to identify adolescents with weight excess and cardiometabolic risk.